1993
DOI: 10.1063/1.353867
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical alloying process of Fe-Cr powders studied by magnetic measurements

Abstract: A mechanical alloying process for a mixture of elemental Fe and Cr powders with the Cr compositions 20-70 at. % was investigated through the measurements of x-ray diffraction, magnetization, and 57Fe Mijssbauer spectrum. We show that magnetic studies provide more detailed information about the alloying process occurring during ball milling than the conventional diffraction techniques in this particular system. A final product after ball milling was identified as a high-temperature phase of the a solid solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 7 publications
2
26
0
1
Order By: Relevance
“…As qualitatively similar results were obtained by Fnidiki et al [24,25] for a series of mechanically alloyed Fe-Cr alloys, Shen et al concluded to the existence of a very 'disordered' Fe-Cr + O + N grain boundary structure [26]. By contrast, a nanocrystalline ferromagnetic bcc-Fe 0.50 Cr 0.50 was obtained by Koyano et al [28] by high-energy ball-milling of elemental powder mixtures during 200 h in argon.…”
Section: E-mail Address: Benilde@ciucpt (Bfo Costa)supporting
confidence: 60%
See 3 more Smart Citations
“…As qualitatively similar results were obtained by Fnidiki et al [24,25] for a series of mechanically alloyed Fe-Cr alloys, Shen et al concluded to the existence of a very 'disordered' Fe-Cr + O + N grain boundary structure [26]. By contrast, a nanocrystalline ferromagnetic bcc-Fe 0.50 Cr 0.50 was obtained by Koyano et al [28] by high-energy ball-milling of elemental powder mixtures during 200 h in argon.…”
Section: E-mail Address: Benilde@ciucpt (Bfo Costa)supporting
confidence: 60%
“…The Mössbauer spectrum of an elemental powder mixture Fe 0.60 Cr 0.40 , milled for 85 h in argon [26], shows, besides the main non-magnetic peak, a weaker and broad magnetic contribution with an average field of ∼12.5 T, much smaller than the field expected for that Cr content. A rather similar Mössbauer spectrum was obtained by Koyano et al [28] with a nanocrystalline Fe 0.50 Cr 0.50 alloy milled for 200 h in argon and further milled under nitrogen. It transformed almost fully into a non-magnetic amorphous phase (Fe 0.50 Cr 0.50 )N 0.058 .…”
Section: Final Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…For Fe-Cr alloys, several studies conducted by ball milling showed their amorphization e.g. [13][14][15][16][17][18][19][20][21]. In particular, in equiatomic or near-equiatomic FeCr alloys milled in vacuum or argon atmosphere, this effect was observed both in alpha and sigma phases, e.g.…”
Section: Methodsmentioning
confidence: 99%